The Health Services (London : C. W. Publishing Ltd.)
1944-05 1944 1940s 23 pages IX. — QUESTIONS FOR DISCUSSION. 1. By what stages has the conception developed of the State's duty to provide, as far as possible, for the health of all citizens? 2. How should preventive medicine be developed? 3. In what ways do the existing health services suffer from lack of co-ordination? 4. How far is the efficiency of the present health services limited by economic considerations? 5. What evidence is there that poverty is still the chief cause of ill-health? 6. From the patient's standpoint, in what ways will medical attention under the proposed Health Service be an improvement upon that obtainable under National Health Insurance? 7. Is there any truth in the claim that the proposed General Practitioner's Service destroys something of social value in the status of doctors? 8. Is there a case for prohibiting private practice altogether? 9. Do the White Paper proposals provide a satisfactory solution to the problem of unifying the hospital service? 10. Are there any other problems untouched or inadequately dealt with in the White Paper? X. — READING LIST. PAMPHLETS. A National Health Service. Cmd. 6502, H.M.S.O. (Summary, 3d.) 1/- Infant Mortality in Scotland. H.M. Stationery Office 1/3 P.E.P. Britain's Health. Pelican Special All pamphlets listed on page 20. 9d. The Health Services (1) Maternity and Child Welfare, School Medical Services and Tuberculosis Services. R.B. Thomas. Fabian Society 1/- The Health Services (2) The Hospital Services. Somerville Hastings. Fabian Society 1/- Health. J.N. Morris. Association for Education in Citizenship......... 4d. BOOKS. Health of the Future. Aleck Bourne. Penguin Special ...................... 9d. The Future of Medicine. D. Stark Murray. Penguin Special 9d. Working Class Wives. Margery Spring-Rice. Pelican 9d. Patent Medicines. Prof. A.J. Clark. Fact 6d. Reform of the Public Health Services. Nuffield College 2/6 Health for All. D. Stark Murray. Gollancz 6/- Birth, Poverty and Wealth. R.M. Titmuss. Hamish Hamilton ............ 7/6 Socialised Medicine in the Soviet Union. Henry E. Sigerist. Gollancz. (Left Book Club) 2/6 The Peckham Experiment, Innes H. Pearse and Lucy H. Crocker. Allen and Unwin 12/6 Order from the SOCIALIST BOOK CENTRE, 48 Essex Street, W.C.2. REMEMBER that finances of C.W. are built on the willingness of members voluntarily to assess themselves to pay additional sums at predetermined intervals over and above subscriptions. Self-assessment forms can be obtained on application from the General Secretary, 4, Gower Street, W.C.1. Published by C.W. Publishing, Ltd., 4, Gower Street, London, W.C.1, and printed by C.P.S., Rutherford Street, Newcastle-on-Tyne. 15X/2/98/10